Total environmental impacts of Japanese material production - Chika Aoki‐Suzuki; Sébastien M. R. Dente; Daisuke Tanaka; Chihiro Kayo; Shinsuke Murakami; Chiharu Fujii; Kiyotaka Tahara; Seiji Hashimoto (Journal of Industrial Ecology, 2021)
Decoupling well‐being from resource use and its associated environmental impacts through resource efficiency and circular economy has become the mainstream agenda for sustainable development. Resource productivity and material flow indicators have been widely used to evaluate resource decoupling. Several approaches have been introduced in Europe to calculate the life cycle environmental impact of resource use at the macro‐level and assess impact decoupling. However, no studies have been conducted to estimate the overall aggregated environmental impact (total environmental impact) associated with resource use in all resource categories using statistical data at the national level and life cycle inventory databases in Japan. This study is the first assessment of the total environmental impact at the national level in Japan, particularly addressing the production process for 213 materials. The study makes it possible to distinguish the 4 phases for environmental impact generation (foreign supply chain, domestic supply chain, production process, and use), 12 environmental impact areas, and the resource category (biomass, fossil, metal, and non‐metallic mineral) of each material. The study shows that there is a higher impact generated by production and foreign supply chain phases in biomass and fossil resources such as crops, livestock, dairy products, and petroleum and coal products as well as some metals (steel and copper). These results imply that measures to reduce resource use and improve energy efficiency in direct production and foreign supply chains through local resource procurement and further resource‐efficient approaches, including the circular economy, should be prioritized for Japan, with its resource‐scarce and manufacturing‐oriented economy.

Correction to: Assessment of Polygala paniculata (Polygalaceae) characteristics for evolutionary studies of legume–rhizobia symbiosis - Yuji Tokumoto; Kayo Hashimoto; Takashi Soyano; Seishiro Aoki; Wataru Iwasaki; Mai Fukuhara; Tomomi Nakagawa; Kazuhiko Saeki; Jun Yokoyama; Hironori Fujita; Masayoshi Kawaguchi (Journal of Plant Research, 2021)
A correction to this paper has been published: https://doi.org/10.1007/s10265-021-01295-3

Assessment of Polygala paniculata (Polygalaceae) characteristics for evolutionary studies of legume–rhizobia symbiosis - Yuji Tokumoto; Kayo Hashimoto; Takashi Soyano; Seishiro Aoki; Wataru Iwasaki; Mai Fukuhara; Tomomi Nakagawa; Kazuhiko Saeki; Jun Yokoyama; Hironori Fujita; Masayoshi Kawaguchi (Journal of Plant Research, 2020)
Root nodule (RN) symbiosis is a mutualistic interaction observed between nitrogen-fixing soil bacteria and nodulating plants, which are scattered in only four orders of angiosperms called nitrogen-fixing clade. Most of legumes engage in RN symbiosis with rhizobia. Molecular genetic analyses with legumes and non-leguminous nodulating plants revealed that RN symbiosis utilizes early signalling components that are required for symbiosis with arbuscular mycorrhizal (AM) fungi. However detailed evolutionary processes are still largely unknown. Comparative analyses with non-nodulating species phylogenetically related to legumes could be better strategies to study the evolution of RN symbiosis in legumes. Polygala paniculata is a non-leguminous species that belongs to a family different from legumes but that is classified into the same order, Fabales. It has appropriate characteristics for cultivation in laboratories: small body size, high fertility and short lifecycles. Therefore, we further assessed whether this species is suitable as a model species for comparative studies with legumes. We first validated that the plant we obtained in Palau was truly P. paniculata by molecular phylogenetic analysis using rbc L sequences. The estimated genome size of this species was less than those of two model legumes, Lotus japonicus and Medicago truncatula . We determined conditions for cultivation in vitro and for hairy root formation from P. paniculata seedlings. It would facilitate to investigate gene functions in this species. The ability of P. paniculata to interact with AM fungi was confirmed by inoculation with Rhizophagus irregularis , suggesting the presence of early signalling factors that might be involved in RN symbiosis. Unexpectedly, branching of root hairs was observed when inoculated with Mesorhizobium loti broad host range strain NZP2037, indicating that P. paniculata has the biological potential to respond to rhizobia. We propose that P. paniculata is used as a model plant for the evolutionary study of RN symbiosis.

Environmental Impact Assessment of Wood Use in Japan through 2050 Using Material Flow Analysis and Life Cycle Assessment - Chihiro Kayo; Sébastien M.R. Dente; Chika Aoki‐Suzuki; Daisuke Tanaka; Shinsuke Murakami; Seiji Hashimoto (Journal of Industrial Ecology, 2019)
Summary In this study, we used material flow analysis and life cycle assessment to quantify the environmental impacts and impact reductions related to wood consumption in Japan from 1970 to 2013. We then conducted future projections of the impacts and reductions until 2050 based on multiple future scenarios of domestic forestry, wood, and energy use. An impact assessment method involving characterization, damage assessment, and integration with a monetary unit was used, and the results were expressed in Japanese yen (JPY). We found that environmental impacts from paper consumption, such as climate change and urban air pollution, were significant and accounted for 56% to 83% of the total environmental impacts between 1970 and 2013. Therefore, reductions of greenhouse gas, nitrogen oxide, and sulfur oxide emissions from paper production would be an effective measure to reduce the overall environmental impacts. An increase in wood use for building construction, civil engineering, furniture materials, and energy production could lead to reductions of environmental impacts (via carbon storage, material substitution, and fuel substitution) amounting to 357 billion JPY in 2050, which is equivalent to 168% of the 2013 levels. Particularly, substitution of nonwooden materials, such as cement, concrete, and steel, with wood products in building construction could significantly contribute to impact reductions. Although an increase of wood consumption could reduce environmental impacts, such as climate change, resource consumption, and urban air pollution, increased wood consumption would also be associated with land‐use impacts. Therefore, minimizing land transformations from forest to barren land will be important.

Physicochemical and Pharmacokinetic Characterization of Amorphous Solid Dispersion of Meloxicam with Enhanced Dissolution Property and Storage Stability - Masanori Ochi; Keisuke Kimura; Atsushi Kanda; Takaki Kawachi; Akitoshi Matsuda; Kayo Yuminoki; Naofumi Hashimoto (AAPS PharmSciTech, 2016)

Paper and Paperboard Demand and Associated Carbon Dioxide Emissions in Asia Through 2050 - Chihiro Kayo; Seiji Hashimoto; Yuichi Moriguchi (Journal of Industrial Ecology, 2012)
Summary This study estimated paper and paperboard demand, pulpwood demand, and carbon dioxide (CO 2 ) emissions from production of paper and paperboard through 2050 in ten Asian countries. Under scenarios of varying population, gross domestic product (GDP), and per capita paper and paperboard demand, we analyzed the relationship between economic growth and consumption of paper and paperboard. We also evaluated options to reduce CO 2 emissions through increased use of black liquor, waste paper pulping, and wood chemical pulping, as well as improvements in pulp, paper, and paperboard production technology. The quadratic curve model (inverted U) for per capita consumption of paper and paperboard against per capita GDP resulted in significant regression coefficients and higher adjusted R 2 values than linear and logarithmic curve models for all uses of paper and paperboard. The estimated paper and paperboard demand in the ten countries in 2050 ranged from 112% (328%) to 156% (454%) of total 2005 consumption for the world (for the ten Asian countries). Of this estimated paper and paperboard demand, China accounted for about 50% and India 20%. The estimated pulpwood demand in these ten countries in 2050 ranged from 13% (48%) to 21% (84%) of global (ten country) 2005 wood supply potential. The introduction or increase of the use of black liquor, waste paper pulping, the combination of wood chemical pulping and black liquor, and technological improvements produced CO 2 reductions of 24%, 5%, 32%, and 25%, respectively, compared to 2050 emission levels in the no‐measure (unadjusted) option, assuming sustainable forest management.